LEGAL REVIEW REGARDING CRIMINAL LIABILITY FOR THE ISSUANCE OF LAND RIGHTS LAWS FOLLOWING A COURT DECISION - Fauzi Rizky (Proceeding International Conference on Social Sciences, 2026)
The aim of criminal law is to protect and safeguard the interests of society. in a balanced manner, such as orderly, peaceful, and prosperous, through the enforcement of justice and crime prevention. This goal is achieved in various ways, including retaliation, general and specific crime prevention, development of criminals to become useful citizens, and rehabilitation social balance is disturbed by crime. This research is normative in nature, it is a legal research method that focuses on analysis of legal norms and statutory regulations, both written written or unwritten. This method uses library studies and secondary data such as laws, court decisions, and doctrines to examine the legal order legal norm system, not field research in order to interpret, explain, and evaluate the law in order to find solutions or provide a basis for establishing new rules. The discussion in this research article is related to the issuance of a legality the basis of the land rights that have been cancelled by the court, so how legal impact or legal responsibility for the holder of legal rights which has been cancelled by a court decision, can it be requested? criminal liability in the criminal offense of embezzlement of land rights in criminal law in order to achieve the objectives of criminal law itself the creation of justice and legal certainty.